Le «voci» composte da mons. Antonio Rimoldi per dizionari ed enciclopedie - Apeciti, Ennio (La Scuola Cattolica, 2025)
Mgr. Antonio Rimoldi public the 297 entries on different encyclopedias and dictionaries, treating in prevalence figures of saints, but not lacking to study many other pages such as the ecumenical councils and the great personalities of the Church, in particular of the Ambrosian, to which Rimoldi belonged. The author analyzes all of these items, placing them, if necessary, in comparison, to highlight their evolution over time, maintaining their chronological division according to their appearance in the works in collaboration, to which they belong. Finally, all of these items are collected for the first time in a full index, which we believe precious for any further research.